Haemoglobin level among pregnant women living at high altitude; Does it need adjustment - Al-Kubaisi, Muna Khaleel Dheyab; M., Bracamonte (2017)
Introduction: High altitude produces significant hypoxia that stimulate hemoglobin to keep the oxygen carrying capacity normal. Haemoglobin (Hb) increases with increased altitude more than 1000 m above sea level. • Hb level may be misleading in pregnant women living at high altitude. • WHO define anaemia as Hb < 11g/dl at sea level. • Hb needs to be adjusted for altitude so as not to misdiagnose anaemia or overestimate the oxygen carrying capacity in those women.